Improvement of spare part arrangement with class based storage method and 5S method in spare part room PT. Wahana Sun Solo (Indomobil Nissan Datsun Solo Baru) - Faros Sambada; Kurniawan Sigit Wahyudi; Zainal Arifin (Universitas Negeri Yogyakarta, 2024)
The aims of the improvements made in the spare part room at PT. Wahana Sun Solo were to: (1) organize the spare parts storage area based on specifications; and (2) increase effectiveness and work efficiency in locating spare parts while creating a work area that adheres to the 5S method standards set by Nissan Motor Indonesia (NMI). The improvements in the spare part room were implemented through several processes: identifying the spare part room layout, redesigning the storage system using a class-based method, updating labels, and designing the improvement of the 5S method. Testing was conducted by performing a time study and a partman movement study focused on locating three sample spare parts: brake pads, air filters, and fan belts. An assessment index was conducted using an evaluation sheet after the improvements were made. The class-based storage method improvement created a more organized arrangement of spare parts according to types. Updates to labeling and enhancements to the 5S method significantly improved the partman's effectiveness and efficiency. Testing demonstrated that the time required to locate brake pad samples resulted in an efficiency increase of 144%, improvement of 218% for air filters, and improvement of 182% for fan belts. Observations showed that, on average, the partman's search required 5 fewer steps for brake pads, 7 fewer steps for air filters, and 5 fewer steps for fan belts compared to the pre-improvement process. In addition, the observation on the movements involved in locating spare parts resulted in reduced movements by at least two movements. The assessment sheet completed after the improvement yielded an assessment index of 91.2%.